Teachers' Perception Toward the English Teaching Material at Elementary Schools In Bengkulu - Eki Saputra (CV. Mitkom Indotama, 2025)
The objective of the research was to investigate the teachers' perception toward the English teaching material at Elementary schools in Bengkulu City. The population of the research was English teachers at Elementary schools in Bengkulu City. This research employed total sampling technique. The instrument used questionnaire. The result of the research showed that (1) teachers' perception toward the English teaching material in Reading, students' reading resources were from English textbooks 59%, English comic for children 70%, English story for children 90%. (2) Teachers' perception in writing: students had to be able to write short sentences 75%. Teachers' perception in speaking: English conversation was dominant 90%. Teachers' perception in listening: English song for children 95%, English short story 95%. (5) Teachers' perception in teaching and supporting media: pictures 85%, (b) textbooks 95%, worksheet 95%, tape recorder 85%, English dictionary 95%, English magazines 85%, English laboratory 85%. Teachers' perception in language components: vocabulary 90%, grammar 95%, pronunciation 75%. Reading, writing, listening, speaking and language components had to be taught at Elementary school students, and teaching and supporting media were needed by the students.